A arte como princípio educativo: uma nova leitura biográfica de Pedro Américo de Figueiredo e Melo - Barros, Francisca Argentina Gois (2006)
In the last twenty years, the historiografic production directed properly toward the History of the Brazilian Education has increased of significant form. The research most recent in this field of study demonstrates that the educators come proceeding the necessary revisions in the treatment from the theoretical questions and method. What also it verifies with the magnifying of the cognitivos procedures, of the search of new objects and new problems, is that the historians of the education are extending its documentary sources, abandoning the accurate affirmations on the past and the future and adopting each time more the retrospect reflections, the autocritic, the reevaluation of the sources, problemize the process of reconstruction of the memories to understand the past in its complexity, density and ambiguity. The elaboration of a new biography of Pedro Américo de Figueiredo e Melo (1843-1905) follows this reasoning and makes to emerge, through exegesis of the literary, philosophical texts and scientific produced by him between1864 and 1905, its participation in the debate enter on the construction of pedagogical boardings for the education of the art, of its defense for the dissemination of the knowledge and the access of the Brazilian population to the national and international artistic production by means of the public and gratuitous school. For being, at the same time, tributary and creditor of the spirit of the time, the literary production of Pedro Américo express conceptual unit, theoretical, aesthetic and ethical that assumes singular importance in our intellectual and educational scene. In this manner, this new biography aims at to contribute for the preservation of the memory of the Brazilian educational history in the second half of XIX century.